The Correlation between Toll Road Development and the Improvement of Local Economy (Case Study: The Soroja Toll Road) - Rahayu, Lisna; Kipuw, Desiree (Unijourn Publisher, 2020)
Most studies assume that road development will improve the economy in the region, as reflected by an increase in Gross Domestic Product (GDP). However, GDP is macro in nature and tends to be biased if we ask who benefits from its increase. To identify whether road development has a positive correlation with the improvement of local economy, hence this study was conducted in a micro context by taking the development of the Soroja Toll Road in Indonesia as a case study. With a length of 10.57 km, connecting Bandung Regency and Bandung City, the newly constructed Soroja Toll Road has a strategic function in supporting activities in the Bandung Metropolitan Area (BMA) and is predicted giving implication on increasing Small and Medium Enterprises (SMEs) profit surrounding its corridor. However, a toll road cannot entirely be seen as a public goods, because not all people have access to this type of infrastructure. Only the users of four-wheeled vehicles and those who can afford to pay the toll charge can access the toll road. This study was aimed at identifying the correlation between the developments of the Soroja Toll Road with the improvement of local economy (SMEs) in its surrounding areas. Based on the analysis result, this study indicates that the presence of the Soroja Toll Road had a bigger positive correlation with the increased profit of medium-sized industries than small-sized industries due to their ability to capture a broader market.